Posttraumatic epilepsy: clinical, diagnostic and therapeutic features - N. E. Maslov; A. A. Litvinova; P. S. Kovalev; N. N. Maslova; N. V. Yuryeva; E. I. Khamtsova (Эпилепсия и пароксизмальные состояния)
According to 2019 statistics records, traumatic brain injuries (TBI) are the most common type of injuries and one of the main causes for disability in Russia. Every year 200 people per 10,000 subjects around the world suffer from serious brain injuries. Severe TBI can result in long-term disability. Posttraumatic epilepsy (PTE) is one of the most dramatic consequences of TBI with an estimated incidence rate ranging from 2% to 50% based on severity of injury. Conducting studies on PTE poses numerous challenges because epilepsy never develops in many patients with TBI or it may occur more than 10 years after TBI.In this review, which includes data from studies conducted by Russian researchers, including us, and foreign colleagues over the last few years (mainly 2017–2022), we analyzed and generalized currently known risk factors, clinical and diagnostic features of PTE in order to increase the awareness about modern methods of laboratory and instrumental diagnostics related to this disease (including electroencephalography and routine/special neuroimaging techniques that allow to identify PTE biomarkers). We also aimed to promote development of preventive strategies for patient management. It has been proved that no clear algorithms for PTE diagnostics and treatment are currently available, which often leads to insufficient patient care.